THE EFFECT OF COMPETENCE AND ORGANIZATIONAL CLIMATE ON DISCIPLINE AND ITS IMPACT ON PERFORMANCE OF COUNTRY CIVIL APPARATUS IN THE REGIONAL FINANCIAL AGENCY OF DISTRICT, DHARMASRAYA - ., Iwan Saputra; Heryanto (Archives of Business Research, 2019)
This study tries to examine the effect of competency, organizational climate and discipline on the performance of state civil apparatus at the Regional Finance Agency in the Regency of Dharmasraya. This study uses descriptive quantitative methods. The study population consisted of 54 people from employees. To obtain a valid and realistic instrument, the validity and reliability test, normality test, multicollinearity test and heterocedasticity test were tested. The data analysis technique used is linear regression analysis, t test, f test, determination coefficient, and path analysis using the SPSS program, with α = 0.05. The results showed that testing the Effect of Competence and Organizational Climate had a partially significant effect on the Discipline Performance of State Civil Apparatus at the Regional Finance Agency of the Regency of Dharmasraya .These empirical findings indicate that competence, organizational climate, and discipline are proven to be well implemented. It is expected that the leadership can maintain the performance of the Regional Financial Apparatus (ASN) of the Regional Finance Agency of the Dharmasraya Regency.